Numerical Simulation of thermal behaviour of buildings (2012)
Numerical simulation of thermal behavior of buildings was carried out with the application of Cooling Load Temperature Difference/Cooling Load Factor (CLTD/CLF) to estimate the energy required for cooling/heating of buildings.This was done to facilitate comparison of the energy being generated from a building while varying significant building parameters. Each factor contributing to space heat gain is described mathematically, considering energy balance within the system. The calculated energy should be overcome by Heating and Ventilation Air-Conditioning (HVAC) system so as to maintain the building interior design temperature and to ensure occupants thermal comfort. The effect of varying significant building parameters like orientation, window glass shade type, number of glass pane used, wall insulation, roof type and floor type on building cooling/heating load was investigated with the use of the developed software. A typical building block was used as a case study for the analysis to arrive at an intelligent decision. The software developed is simple to use, needs fewer input data compared to other software developed for similar task. All the earlier mentioned advantages are without sacrificing accuracy and reliability.